ANALISIS PENGARUH INFLASI DAN PENDAPATAN TERHADAP KONSUMSI MASYARAKAT DI PROVINSI SUMATERA UTARA - Tiara Marsya Aulya; Dia Aulia Harahap, Nurul Mardiah (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to determine the analysis of the eflect of inflation and income on consumption in North Sumatra Province. The analysis method used in this study is a quantitative-descriptive method, with testing of instrument validity, instrument reliability, significance testing such as the T Test, Determination Test, and hypothesis testing. The independent variables used in this study are inflation and income, and the dependent variable is community consumption. Overall, the independent variables (inflation and national income) have a positive eflect on community consumption. Based on the equation, it can be seen that the most influential independent variable is the income variable with a coefficient of 0.501, followed by the inflation variable with a coefficient of 0.381. Every increase in the score of the inflation variable (X1) will encourage an increase in community consumption (Y) by 0.381. Meanwhile, every increase in the score of the income variable (X2) will encourage community consumption (Y) by 0.501.